1971 Facts and Fiction - Afrasiab (Rawalpindi Services Book Club, 2014)
Way back in the century during the ming dynasty,the great muslim Admiral of the chines fleet,Zheng He (1371 AD -1433AD),who is said to have discoverd Americas Even before Chistpher Cloumbs,stopped over at chittagong during one of his seven voyages across the world.
Bibliography
Keywords: 1971 Facts And Fiction -- History -- Historical issue -- India And Bangladesh After 1971